PROMOSI KESEHATAN ORGAN REPRODUKSI PADA REMAJA DUSUN SYAMTALIRA BAYU ACEH UTARA - Zahara, Cut Ita; Amalia, Ika; Maqfira, Yulina; Amanda, Feby Zea; Agina Putri S, Theresia; Nurjannah, Siti; Nurhidayah, Nurhidayah (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
Promoting reproductive organ health among adolescents is crucial given the crucial developmental phase in their lives. This study aims to analyze the effectiveness of various approaches in promoting adolescent reproductive organ health. The methods used include surveys, interviews, and secondary data analysis. The results indicate that an approach integrating comprehensive sexual education with reproductive health services proves most successful in improving knowledge and healthy behaviors among adolescents. Factors such as accessibility, self-confidence, and social support also play important roles in the success of this health promotion. Policy implications include expanding sexual education programs in schools and increasing access to reproductive health services for adolescents. Further research is needed to evaluate the long-term reach and holistic impact of promoting reproductive organ health among adolescents. Keywords: Adolescents, Reproductive Organ Health, Health Promotion